Prediction of area impacted by debris flow under vertical rainfall distribution: a case study of Xulong Gully in the upper reaches of the Jinsha River - Peng, Wei; Sun, Xiaohui; Tang, Li (Frontiers in Earth Science, 2025)
Debris flow, as a highly destructive geological hazard, requires accurate prediction of its impacted area for effective disaster prevention and mitigation. However, when predicting debris flow-affected area in small watersheds influenced by micro-topography and microclimate, the role of vertical rainfall distribution characteristics is often overlooked. This study examines the influence of heterogeneous rainfall—a complex factor—on the area impacted by debris flows. Taking Xulong Gully as a case, we fit precipitation data using a mountainous vertical rainfall distribution formula, calculate runoff via the soil conservation service curve number method (SCS-CN) method, compute runoff peak discharge using the isochrone method, the runoff peak discharge is used for computing the solid-liquid peak discharge of the input hydrograph, and predict impact ranges with the finite volume-based SFLOW software. Results are compared with those from traditional methods and those obtained using the inverse distance weighting (IDW) method for rainfall distribution. Analysis shows that the maximum error in fitting daily maximum rainfall using the mountainous precipitation vertical distribution formula (Gaussian curve) for Xulong Gully is 11.90%. This acceptable error indicates that the formula is suitable for watersheds with pronounced vertical rainfall distribution patterns. The debris flow, calculated using the methodology outlined above with the mountainous rainfall formula as input, can rush out of the gully mouth, form a large-scale deposit fan, and block the Jinsha River channel. By contrast, debris flows simulated by traditional methods (following DZ/T 0020-2006) and the IDW method (for rainfall extrapolation) are confined to the main gully and do not reach the gully mouth. This finding indicates that the IDW and code-based methods underestimate the debris flow hazard in Xulong Gully. This study integrates the mountainous precipitation vertical distribution formula with the SCS-CN method, isochrone method, and SFLOW simulation to predict debris flow impact areas under heterogeneous rainfall. The approach has significant practical value for small watersheds, including Xulong Gully, where micro-topography and micro-climate effects are notable.